The possibility of establishing the dimensions of the quality of banking service: for the Rasheed and Rafidain bankers in Salah al-Din (model) Study: An exploratory - noaman abdulah, mazen; salEM Ghanem, saad; sobah chaair, Hader (Journal of Excellence for Economics and Management Research, 2020)
Abstract: This study aims at identifying the quality dimensions of banking service and the extent to which the banks in question are committed to quality assurance in providing their services. The main research hypothesis was developed in accordance with research objectives. Hence, (39) copies of the questionnaire were distributed to employees of Al-Rasheed and Al-Rafidain banks. The hypothesis was tested using a set of statistical tools for research variables. The study concluded that there is a difference in attention and commitment of banks under study in terms of quality dimensions of banking services. According to the findings of this study, a set of recommendations were presented in order to develop the work of banks under study. The most important recommendation is that banks covered have to pay adequate and equal attention to the quality dimensions of banking services in order to accomplish their goals in achieving excellence over competitors.